Induction of IL‐1β and antimicrobial peptides as a potential mechanism for topical dithranol. Issue 6 (25th February 2021) - Benezeder, Theresa; Gehad, Ahmed; Patra, VijayKumar; Clark, Rachael; Wolf, Peter
Abstract: Topical dithranol is effective in autoimmune conditions like alopecia areata, inducing hair regrowth in a high percentage of cases. Exact mechanisms of dithranol in alopecia areata, with seemingly healthy epidermis besides altered hair follicles, are not well understood. To better understand dithranol's mechanisms on healthy skin, we analysed its effect on normal murine as well as xenografted human skin. We found a strong increase in mRNA expression of anti‐microbial peptides (AMPs) (eg Lcn2, Defb1, Defb3, S100a8, S100a9 ), keratinocyte differentiation markers (eg Serpinb3a, Flg, Krt16, Lce3e ) and inflammatory cytokines (eg Il1b and Il17 ) in healthy murine skin. This effect was paralleled by inflammation and disturbed skin barrier, as well as an injury response resulting in epidermal hyperproliferation, as observed in murine and xenografted adult human skin. This contact response and disturbed barrier induced by dithranol might lead via a vicious loop between AMPs such as S100a8/a9 (that led to skin swelling itself after topical application) and cytokines such as IL‐1β to an immune suppressive environment in the skin. A better understanding of the skin's physiologic response to dithranol may open up new avenues for the establishment of novel therapeutics (including AMP‐related/interfering molecules) for certain skin conditions, such as alopecia areata.